Relationship Between Educational Level and Knowledge in Self-Medication of Diarrhea Disease Disease in Children - Sari, Ferika Indra; Toyo, Eleonora Maryeta; Munawaroh, Siti; Akbar, Nanda Dwi (Indonesian Journal of Global Health Research, 2024)
In Indonesia, diarrhea is the second killer of toddlers after ISPA and 10,000 toddlers die from diarrhea every year. Proportion of diarrhea cases in Central Java in 2014 was 79.8%. The main options for seeking recovery from an illness include seeking treatment at a health service center or treating yourself. increasing knowledge about diarrhea, it is necessary to provide health education. The purpose of this study was to determine the relationship between the level of education with the level of knowledge of self-medication of diarrhea in children as parents in Bae District, Kudus Regency. Method: The purpose of research was to decide the relationship among the level of education and the level of knowledge of diarrhea self-medication in children as parents in Bae District, Kudus Regency. The research was called a quantitative research by a cross sectional approach. The population were all people in Bae District, Kudus Regency. The design of this research was quantitative analysis through a proportional sampling technique. The instrument is applied a questionnaire on a sample of 400 respondents in the community in Bae sub-district. The data analysis used in this study begins by using a validity test to measure whether a questionnaire is valid or not; reliability test to measure whether a questionnaire is consistent or stable over time. Furthermore, the One Sample Kolmogorov Smirnov test was carried out to see that the data was normally distributed and the Spearman rank test to determine the relationship or influence between two ordinal scale variables. Results and Conclusions: The results showed a significant relationship between education level and parental knowledge in self-medication for diarrheal disease in children with a correlation coefficient of 0.928, so it is included in the very strong category and the results are significant.